The Functional Effects of Key Driver KRAS Mutations on Gene Expression in Lung Cancer - Zhang, Jisong; Hu, Huihui; Xu, Shan; Jiang, Hanliang; Zhu, Jihong; Qin, E.; He, Zhengfu; Chen, Enguo (Frontiers in Genetics, 2020)
Lung cancer is a common malignant cancer. Kirsten rat sarcoma oncogene (KRAS) mutations have been considered as a key driver for lung cancers. KRAS p.G12C mutations were most predominant in NSCLC which was comprised about 11%–16% of lung adenocarcinomas (p.G12C accounts for 45%–50% of mutant KRAS). But it is still not clear how the KRAS mutation triggers lung cancers. To study the molecular mechanisms of KRAS mutation in lung cancer. We analyzed the gene expression profiles of 156 KRAS mutation samples and other negative samples with two stage feature selection approach: (1) minimal Redundancy Maximal Relevance (mRMR) and (2) Incremental Feature Selection (IFS). At last, 41 predictive genes for KRAS mutation were identified and a KRAS mutation predictor was constructed. Its leave one out cross validation MCC was 0.879. Our results were helpful for understanding the roles of KRAS mutation in lung cancer.